Productivity and residual effects of legumes in ricebased cropping systems in a warmtemperate environment II. Residual effects on rice - Schulz, S.; Keatinge, J.D.H.; Wells, G.J. (1999)
Field experiments were conducted over the period 1994–1996 to investigate the residual effect on rice of a wide range of temperate legume species, grown during the preceding winter season in a warm-temperate environment in Nepal. The incorporation of large quantities of above- and below-ground legume biomass (roots and foliage) resulted in substantial residual effects on the subsequent upland rice crop. The effects on rice yield in terms of percent increase over the control were more pronounced at a site of comparatively lower inherent soil fertility where grain yields of rice grown after high yielding legume crops such as bitter lupin (Lupinus mutabilis) and Persian clover (Trifolium resupinatum) were almost twice as high (up to 7.6 t DM ha−1) than those of the control treatment (rice after wheat). In contrast, the residual effects of below-ground biomass (roots, nodules) on the following rice crop were not very pronounced and resulted in similar residual effects as rice, after fallow. Although up to 480 kg ha−1 of legume foliage N had been applied to rice, only a small proportion of the legume N (up to 70 kg N ha−1) was recovered by the following rice crop. Total rice dry matter yields were highly correlated with the amount of legume N applied, yet other factors such as residue quality and residue management practices appeared to also affect the magnitude of the residual effects. Future work should aim at investigating the effect of residue quality as affected by legume species and residue management practice on decomposition and N mineralisation processes in rice soils.